Two species of hackled-orb web spider genus Hyptiotes (Araneae, Uloboridae) from Guangxi, China - Huang, Zongguang; Yin, Haiqiang; Cai, Qu; Xu, Xiang (Zootaxa, 2023)
Two species of the genus Hyptiotes Walckenaer 1837 are described from Guangxi Zhuang Autonomous Region, China, including a new species, Hyptiotes nonggang n. sp. (♂♀), and a known species, Hyptiotes paradoxus (C. L. Koch, 1834) (♂♀) which is the type species. Detailed descriptions and illustrations of the two species are provide, and a map of collecting localities of them in China is also provided.